The Effect of Budget Efficiency and Online Absence System on ASN Performance in the Department of Food Crop, Horticulture and Plantations of Sungai Penuh City with Motivation as an Intervening Variable - Andes Prayuda Yunanda; Elfiswandi Elfiswandi; Lusiana Lusiana (Jurnal Multidisiplin Sahombu, 2026)
This study aims to examine the influence of budget efficiency and an online attendance system on the performance of civil servants (ASN) at the Food Crops, Horticulture, and Plantation Service in Sungai Banyak City, with motivation as an intervening variable. Data collection methods included a survey and questionnaire distribution, with a sample of 100 respondents. The analysis method used was structural equation modeling using SmartPLS. The results showed a significant effect of budget efficiency on motivation. There was a significant effect of the online attendance system on motivation. There was a significant effect of budget efficiency on performance. There was a significant effect of the online attendance system on performance. There was a significant effect of motivation on performance. Motivation mediates the effect of budget efficiency on performance. Motivation mediated the effect of the online attendance system on performance.